Flash evaporation non-woven sheet and processing method thereof
By adding nano-zinc sulfide and clay-like multilayer titanium carbide to flash-spun sheets, a composite material is formed, which solves the problem of high oxygen permeability, improves barrier properties and mechanical properties, and expands the application range.
Patent Information
- Application Number
- CN202410455521.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-16
- Publication Date
- 2025-10-24
AI Technical Summary
The high oxygen permeability of existing flash-spun sheets limits their application in food, pharmaceutical, electronic components, and modified atmosphere packaging fields, and the problem of high oxygen permeability has not been effectively solved in existing patents.
By adding nano-zinc sulfide and clay-like multilayer titanium carbide to the spinning solvent, a composite material is formed. The size effect and physical barrier effect of nano-zinc sulfide, as well as the layered structure of clay-like multilayer titanium carbide, form an interwoven barrier network to reduce oxygen permeability.
It significantly improves the oxygen barrier properties of the sheet, enhances the mechanical properties of the material, extends its service life, and expands its application range.
Smart Images

Figure CN120830185A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of textile production, in particular to a flash-spun nonwoven sheet and a processing method thereof. BACKGROUND
[0002] The flash-spun technology was first developed by Herbert Blades of DuPont in 1957 and has since been commercially applied to the production of high-performance materials such as the Tyvek brand. Fibers obtained by flash spinning have good physical and chemical properties, and also provide new possibilities for the innovation of nonwoven materials. For flash-spun sheet products, the high oxygen transmission rate of the sheet will cause the following problems: food packaging problems: food oxidation spoilage: For food packaging materials, high oxygen transmission rate will cause the oxygen content inside the package to be too high, and the oil, fat, vitamins, etc. in the food will easily oxidize, causing problems such as deterioration of food flavor, reduction of nutritional value, color change, and spoilage. Shortened shelf life: The presence of oxygen will accelerate the reproduction of microorganisms and enzymatic reactions, shortening the shelf life of food. Drug packaging problems: loss of efficacy: For some drugs, oxygen may cause the active ingredients to degrade or lose efficacy, reducing the efficacy of the drug. Safety issues: Some drugs may produce harmful byproducts when exposed to oxygen, posing a threat to patient health. Electronic component packaging: oxidation failure: Electronic components may undergo oxidation reactions when exposed to oxygen, affecting the performance and lifespan of the components. Modified atmosphere packaging: imbalance of atmosphere: High oxygen transmission rate will disrupt the pre-set gas balance inside the package, affecting the storage and transportation conditions of the packaged items. Other applications: increased energy consumption: In cold storage, insulation, or thermal insulation packaging, high oxygen transmission rate will cause the cold or heat to be lost more quickly, increasing energy consumption. Decreased visual quality: For some packaging products that require transparency, high oxygen transmission rate may cause the packaging material to yellow and age, affecting the visual appeal of the product. There is an urgent need to develop a new product to overcome the above technical problems and narrow the application field. The present application mainly modifies the spinning raw material to solve the above technical problems.
[0003] Chinese Patent Publication No. CN114687057B relates to a flash-spun sheet and its application, characterized in that the raw material of the flash-spun sheet is polyethylene and a modifier; the attenuation value ΔC of the bending length of the flash-spun sheet is 0.1-0.4; ΔC = 1-C2 / C1; C1 is the bending length of the flash-spun sheet before aging treatment; C2 is the bending length of the flash-spun sheet after aging treatment; the bending length C2 of the flash-spun sheet after aging treatment is 4-10 cm. The flash-spun sheet of the present application has lower decline in bending length while maintaining brightness, which can prolong the service life of the product and expand the application range.
[0004] CN115537959B relates to a composite material, characterized in that the raw material of the composite material comprises polyethylene; the shrinkage rate R is 0.2-0.7; the standard heat shrinkage strength σr is 0.5-3.5 N / mm2; and the mildew-proof grade is less than 2. The application has good shrinkage performance and better antibacterial and mildew-proof effect, and therefore has wide application.
[0005] CN114108112B relates to a polyethylene sheet, characterized in that the aging rate of tensile strength △S is 0.10-0.30; △S=1-S2 / S1; S1 is the tensile strength of the non-woven fabric before aging treatment, in units of kN / m; S2 is the tensile strength of the non-woven fabric after aging treatment, in units of kN / m; the process conditions of aging treatment are: irradiance in the wavelength range of 300-400 nm is 60±2 w / m2, black tag temperature is 65±2℃, air temperature of the test bin is 38±3℃, relative humidity is 50±10%, and drying time is 1440 hours. The product of the application still has good tensile strength after aging, thereby prolonging the service life of the product.
[0006] CN116590846B relates to a flash-spun polyethylene film material with better toughness and a manufacturing method thereof, the raw material of which comprises polyethylene; the grammage G of the flash-spun polyethylene film material is greater than 50 g / m2; the initial toughness Z0 of the flash-spun polyethylene film material is 20-35 (N·m) / g; Z0=[RM×EM+RT×ET] / G; wherein: RM is the tensile strength in the MD direction; RT is the tensile strength in the TD direction; EM is the tensile elongation in the MD direction; ET is the tensile elongation in the TD direction; the flash-spun polyethylene film material is exposed to a dry heat atmosphere at 90℃ for 6 hours, and then cooled at 25℃ and a relative humidity of 65% for 24 hours; then the light transmittance is measured to be 8%-13%; the light transmittance is tested according to GBT2410-2008, and the light transmittance is the ratio of the light flux passing through the sample to the light flux incident on the sample, expressed as a percentage. The application has wide application prospects in the fields of packaging agriculture and the like due to the better toughness.
[0007] The above patent documents do not involve the technical problem of oxygen transmission rate, and do not propose a solution to similar problems. SUMMARY
[0008] The purpose of the present application is to overcome the shortcomings of the prior art and provide a processing method for flash-spun non-woven sheet material.
[0009] The purpose of the present application is achieved by the following technical solutions:
[0010] A flash nonwoven sheet material, characterized in that the raw material of the sheet material comprises polyethylene, the gram weight of the sheet material is greater than 50 g / m 2 ;
[0011] The oxygen transmission rate of the sheet material is 1.5*10 10 ~3*10 10 cm 3 / (m 2 *24h*0.1MPa);
[0012] The oxygen transmission coefficient of the sheet material is 2*10 6 ~5*10 6 cm 3 / (m*24h*0.1MPa);
[0013] The oxygen transmission rate and the oxygen transmission coefficient are GB / T19789-2021 Test method for oxygen transmission of plastic film and sheet for packaging by coulometric detection.
[0014] The longitudinal tensile strength of the sheet material is greater than 5KN / m. The test standard is GBT 12914-2018.
[0015] The oxygen transmission rate of the sheet material is 1.5*10 10 ~2*10 10 cm 3 / (m 2 *24h*0.1MPa).
[0016] The oxygen transmission rate of the sheet material is 2*10 10 ~2.5*10 10 cm 3 / (m 2 *24h*0.1MPa).
[0017] The oxygen transmission rate of the sheet material is 2.5*10 10 ~3*10 10 cm 3 / (m 2 *24h*0.1MPa).
[0018] The oxygen transmission coefficient of the sheet material is 2*10 6 ~2.5*10 6 cm 3 / (m*24h*0.1MPa).
[0019] The oxygen transmission coefficient of the sheet material is 2.5*10 6 ~3*10 6 cm 3 / (m*24h*0.1MPa).
[0020] The oxygen transmission coefficient of the sheet is 3*10 6 ~ 3.5*10 6 cm 3 / (m*24h*0.1MPa).
[0021] The oxygen transmission coefficient of the sheet is 3.5*10 6 ~ 4*10 6 cm 3 / (m*24h*0.1MPa).
[0022] The oxygen transmission coefficient of the sheet is 4*10 6 ~ 4.5*10 6 cm 3 / (m*24h*0.1MPa).
[0023] The oxygen transmission coefficient of the sheet is 4.5*10 6 ~ 5*10 6 cm 3 / (m*24h*0.1MPa).
[0024] The gram weight of the sheet is less than 150g / m 2 .
[0025] The gram weight of the sheet is less than 120g / m 2 .
[0026] The gram weight of the sheet is less than 100g / m 2 .
[0027] A processing method of flash nonwoven sheet, comprising the technical steps of:
[0028] I. Disperse nano-zinc sulfide and clay-like multi-layer titanium carbide in spinning solvent to obtain spinning solvent containing functional particles;
[0029] II. Disperse polymer in the spinning solvent containing functional particles prepared in step I to obtain flash spinning solution;
[0030] The mass fraction of polymer in the flash spinning solution is 8-11%.
[0031] The mass ratio of nano-zinc sulfide to clay-like multi-layer titanium carbide is 1:1.
[0032] The mass fraction of nano-zinc sulfide in the mixture of polymer, nano-zinc sulfide and clay-like multi-layer titanium carbide is 1%-3%.
[0033] The particle size of nano-zinc sulfide is between 20-40 nanometers.
[0034] The clay-like multi-layer titanium carbide has a clay-like multi-layer structure and a purity of greater than or equal to 98%.
[0035] The polymer is polyethylene;
[0036] The spinning solvent is a mixture of several kinds of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, unsaturated hydrocarbons, halogenated hydrocarbons, alcohols, esters, ethers, ketones, nitriles, amides, fluorocarbons;
[0037] III. The flash spinning is carried out to obtain flash fibers, and the flash fibers are laid and hot-pressed to obtain a flash nonwoven sheet.
[0038] The barrier property of the nanometer zinc sulfide in the raw material of the present application is improved: (1) size effect: the small size of the nanometer zinc sulfide particles can effectively fill the pores in the polymer matrix, reducing the diffusion path of oxygen gas, thereby improving the barrier property of the material. (2) Physical barrier effect: zinc sulfide nanoparticles can act as a physical barrier to slow down the speed of oxygen and other gas molecules penetrating the polymer matrix. In general, zinc sulfide can not only enhance the mechanical properties of the material by optimizing the microstructure and interface properties of the composite material, but also improve the barrier property by physically filling and improving the continuity of the matrix. At the same time, its own optical properties also help to achieve the expected barrier effect in specific applications. When the nanometer zinc sulfide particles are uniformly dispersed in the polymer matrix, the interface interaction between the particles and the matrix can enhance the mechanical properties of the matrix. Zinc sulfide nanoparticles are equivalent to "reinforcing fibers" that can disperse and prevent crack propagation under stress, thereby improving the tensile strength, bending strength and hardness of the composite material.
[0039] The clay-like multi-layer titanium carbide in the raw material of the present application can form an interlaced barrier network in the polymer matrix due to its unique layered structure, which can effectively limit the diffusion path of oxygen gas molecules, thereby improving the barrier property of the material. At the same time, due to the high chemical stability and low oxygen gas permeability of titanium carbide, it can maintain its barrier effect well even in extreme environments.
[0040] Compared with the prior art, the positive effects of the present application are:
[0041] The sheet material of the present application has good oxygen barrier effect. BRIEF DESCRIPTION OF DRAWINGS
[0042] Figure 1 SEM image of Example 2. DETAILED DESCRIPTION
[0043] The following provides a specific embodiment of a flash nonwoven sheet of the present application.
[0044] Example 1
[0045] A processing method of flash nonwoven sheet, comprising the technical steps of:
[0046] I. Disperse nano-zinc sulfide and clay-like multi-layer titanium carbide in a spinning solvent to obtain a spinning solvent containing functional particles;
[0047] II. Disperse a polymer in the spinning solvent containing functional particles prepared in step I to obtain a flash spinning solution;
[0048] The mass fraction of the polymer in the flash spinning solution is 8%.
[0049] The mass ratio of nano-zinc sulfide to clay-like multi-layer titanium carbide is 1:1.
[0050] The mass fraction of nano-zinc sulfide in the mixture of polymer, nano-zinc sulfide and clay-like multi-layer titanium carbide is 1%.
[0051] The particle size of nano-zinc sulfide is between 20-40 nanometers.
[0052] The clay-like multi-layer titanium carbide has a clay-like multi-layer structure and a purity of greater than or equal to 98%.
[0053] The polymer is polyethylene.
[0054] The spinning solvent is a mixture of dichloromethane, 1,1-dichloro-1-chloroethane and 2,3-dihydrodecafluoropentane, and the mass ratio of the three is 7:2:1.
[0055] III. Perform flash spinning on the flash spinning solution, the spinning temperature is 200-230°C, to obtain flash fibers, and then perform web laying and hot pressing on the flash fibers to obtain a flash nonwoven sheet.
[0056] The test results of Example 1 are shown in Table 1.
[0057] Example 2
[0058] A processing method of flash nonwoven sheet, comprising the technical steps of:
[0059] I. Disperse nano-zinc sulfide and clay-like multi-layer titanium carbide in a spinning solvent to obtain a spinning solvent containing functional particles;
[0060] II. Disperse a polymer in the spinning solvent containing functional particles prepared in step I to obtain a flash spinning solution;
[0061] The mass fraction of the polymer in the flash spinning solution is 9%.
[0062] The mass ratio of nano-zinc sulfide to clay-like multi-layer titanium carbide is 1:1.
[0063] The mass fraction of nano-zinc sulfide in the mixture of the polymer, nano-zinc sulfide and clay-like multi-layer titanium carbide is 2%.
[0064] The nano-zinc sulfide has a particle size of 20-40 nanometers.
[0065] The clay-like multi-layer titanium carbide has a clay-like multi-layer structure and a purity of greater than or equal to 98%.
[0066] The polymer is polyethylene.
[0067] The spinning solvent is a mixture of dichloromethane, 1,1-dichloro-1-chloroethane and 2,3-dihydrodecafluoropentane, and the mass ratio of the three is 7:2:1.
[0068] III. The flash spinning is carried out to obtain flash fibers, and the flash fibers are laid and hot-pressed to obtain a flash non-woven sheet.
[0069] The test results of this embodiment 2 are shown in Table 1. Figure 1 The SEM image of the application can be seen that the inorganic particles are partially filled into the gaps of the flash fibers.
[0070] Embodiment 3
[0071] A processing method of a flash non-woven sheet, which comprises the following technical steps:
[0072] I. Disperse nano-zinc sulfide and clay-like multi-layer titanium carbide in a spinning solvent to obtain a spinning solvent containing functional particles;
[0073] II. Disperse a polymer in the spinning solvent containing functional particles prepared in step I to obtain a flash spinning solution;
[0074] The mass fraction of the polymer in the flash spinning solution is 10%.
[0075] The mass ratio of nano-zinc sulfide to clay-like multi-layer titanium carbide is 1:1.
[0076] The mass fraction of nano-zinc sulfide in the mixture of the polymer, nano-zinc sulfide and clay-like multi-layer titanium carbide is 3%.
[0077] The nano-zinc sulfide has a particle size of 20-40 nanometers.
[0078] The clay-like multi-layer titanium carbide has a clay-like multi-layer structure and a purity of greater than or equal to 98%.
[0079] The polymer is polyethylene.
[0080] The spinning solvent is a mixture of dichloromethane, 1,1-dichloro-1-chloroethane and 2,3-dihydrodecafluoropentane, and the mass ratio of the three is 7:2:1.
[0081] III. The flash spinning is carried out to obtain flash fibers, and the flash fibers are laid and hot-pressed to obtain a flash nonwoven sheet.
[0082] The test results of this example 3 are shown in Table 1.
[0083] Comparative example 1
[0084] A processing method of a flash nonwoven sheet, which comprises the following technical steps:
[0085] I. Disperse nano-zinc sulfide in a spinning solvent to obtain a spinning solvent containing functional particles;
[0086] II. Disperse a polymer in the spinning solvent containing functional particles prepared in step I to obtain a flash spinning solution;
[0087] The mass fraction of the polymer in the flash spinning solution is 9%.
[0088] The mass fraction of the nano-zinc sulfide in the mixture of the polymer and the nano-zinc sulfide is 2%.
[0089] The nano-zinc sulfide has a particle size of 20-40 nm.
[0090] The polymer is polyethylene;
[0091] The spinning solvent is a mixture of dichloromethane, 1,1-dichloro-1-chloroethane and 2,3-dihydrodecafluoropentane, and the mass ratio of the three is 7:2:1.
[0092] III. The flash spinning is carried out to obtain flash fibers, and the flash fibers are laid and hot-pressed to obtain a flash nonwoven sheet.
[0093] The test results of this comparative example 1 are shown in Table 1.
[0094] Comparative example 2
[0095] A processing method of a flash nonwoven sheet, which comprises the following technical steps:
[0096] I. Disperse clay-like multi-layer titanium carbide in a spinning solvent to obtain a spinning solvent containing functional particles;
[0097] II. Disperse a polymer in the spinning solvent containing functional particles prepared in step I to obtain a flash spinning solution;
[0098] The mass fraction of the polymer in the flash spinning solution is 9%.
[0099] The mass fraction of the clay-like multi-layer titanium carbide in the mixture of the polymer, the clay-like multi-layer titanium carbide, and the mixture of the two is 2%.
[0100] The nano-zinc sulfide has a particle size of 20-40 nanometers.
[0101] The clay-like multi-layer titanium carbide has a clay-like multi-layer structure and a purity of greater than or equal to 98%.
[0102] The polymer is polyethylene.
[0103] The spinning solvent is a mixture of dichloromethane, 1,1-dichloro-1-chloroethane, and 2,3-dihydrodecafluoropentane in a mass ratio of 7:2:1.
[0104] III. The flash spinning is performed to obtain flash fibers, and the flash fibers are laid and hot-pressed to obtain a flash non-woven sheet.
[0105] The test results of the comparative example 2 are shown in Table 1.
[0106] Comparative example 3
[0107] A processing method of a flash non-woven sheet, which comprises the following technical steps:
[0108] I. The nano-zinc sulfide and the clay-like multi-layer titanium carbide are dispersed in a spinning solvent to obtain a spinning solvent containing functional particles.
[0109] II. The polymer is dispersed in the spinning solvent containing functional particles prepared in step I to obtain a flash spinning solution.
[0110] The mass fraction of the polymer in the flash spinning solution is 9%.
[0111] The mass ratio of the nano-zinc sulfide to the clay-like multi-layer titanium carbide is 1:1.
[0112] The mass fraction of the nano-zinc sulfide in the mixture of the polymer, the nano-zinc sulfide, and the clay-like multi-layer titanium carbide is 0.5%.
[0113] The nano-zinc sulfide has a particle size of 20-40 nanometers.
[0114] The clay-like multi-layer titanium carbide has a clay-like multi-layer structure and a purity of greater than or equal to 98%.
[0115] The polymer is polyethylene.
[0116] The spinning solvent is a mixture of dichloromethane, 1,1-dichloro-1-chloroethane and 2,3-dihydrodecafluoropentane, and the mass ratio of the three is 7:2:1;
[0117] III. The flash spinning is carried out to obtain flash fibers, and the flash fibers are laid and hot-pressed to obtain a flash nonwoven sheet.
[0118] The test results of the present comparative example 3 are shown in Table 1.
[0119] Table 1: Test data table of the present application
[0120]
[0121] The above only describes the preferred embodiments of the present application, and it should be noted that, for those skilled in the art, without departing from the concept of the present application, a number of improvements and refinements can be made, which should also be considered within the protection scope of the present application.
Claims
1. A flash-spun nonwoven sheet material characterized by, The raw material of the sheet comprises polyethylene, the gram weight of the sheet is greater than 50 g / m 2 ; The oxygen transmission rate of the sheet is 1.5*10 10 ~3*10 10 cm 3 / (m 2 *24h*0.1MPa); The oxygen transmission coefficient of the sheet is 2*10 6 ~5*10 6 cm 3 (m*24h*0.1MPa); The oxygen transmission rate and the oxygen transmission coefficient are determined by GB / T 19789-2021 Coulometric Detection Method for Oxygen Transmission of Plastic Film and Sheet.
2. A flash-spun nonwoven sheet material according to claim 1, wherein The oxygen transmission rate of the sheet is 1.5*10 10 ~2*10 10 cm 3 / (m 2 *24h*0.1MPa).
3. A flash-spun nonwoven sheet material according to claim 1, wherein The oxygen transmission rate of the sheet is 2*10 10 ~ 2.5*10 10 cm 3 / (m 2 * 24h * 0.1 MPa).
4. A flash-spun nonwoven sheet material according to claim 1, wherein The oxygen transmission rate of the sheet is 2.5*10 10 ~3*10 10 cm 3 / (m 2 *24h*0.1MPa).
5. A flash-spun nonwoven sheet material according to claim 1, wherein The oxygen transmission coefficient of the sheet is 2*10 5 ~ 2.5*10 6 cm 3 (m*24h*0.1MPa).
6. A flash-spun nonwoven sheet material according to claim 1, wherein The oxygen transmission coefficient of the sheet is 2.5*10 6 ~3*10 6 cm 3 / (m*24h*0.1MPa).
7. A flash-spun nonwoven sheet material according to claim 1 wherein, The oxygen transmission coefficient of the sheet is 3*10 6 ~ 3.5*10 6 cm 3 (m*24h*0.1MPa).
8. A flash-spun nonwoven sheet material according to claim 1 wherein, The oxygen transmission coefficient of the sheet is 3.5*10 6 ~4*10 6 cm 3 / (m*24h*0.1MPa).
9. A flash-spun nonwoven sheet material according to claim 1 wherein, The oxygen transmission coefficient of the sheet is 4*10 6 ~ 4.5*10 6 cm 3 / (m*24h*0.1MPa).
10. A flash-spun nonwoven sheet material according to claim 1, wherein The oxygen transmission coefficient of the sheet is 4.5*10 6 ~5*10 6 cm 3 / (m*24h*0.1MPa).
11. A flash-spun nonwoven sheet material according to claim 1, wherein The grammage of the sheet is less than 150 g / m 2 .
12. A flash-spun nonwoven sheet material according to claim 1 wherein, The grammage of the sheet is less than 120 g / m 2 .
13. A flash-spun nonwoven sheet material according to claim 1 wherein, The grammage of the sheet is less than 100 g / m 2 .
14. A method of processing a flash-spun nonwoven sheet material, characterized by, The technical steps comprise: I. dispersing nano-zinc sulfide and clay-like multi-layer titanium carbide in a spinning solvent to obtain a spinning solvent containing functional particles; II. dispersing a polymer in the spinning solvent containing functional particles prepared in step I to obtain a flash spinning solution; III. performing flash spinning on the flash spinning solution prepared in step II at a spinning temperature of 200-230 DEG C to obtain flash fibers, and then performing webbing and hot pressing on the flash fibers to obtain a flash nonwoven sheet.
Citation Information
Patent Citations
A polyethylene sheet
CN114108112B
A flash evaporation sheet and its application
CN114687057B
A composite material
CN115537959B
A flash-spun polyethylene film material with better toughness and its manufacturing method
CN116590846B